2006
DOI: 10.1074/jbc.m602110200
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-derived Factor Inhibits Advanced Glycation End Product-induced Retinal Vascular Hyperpermeability by Blocking Reactive Oxygen Species-mediated Vascular Endothelial Growth Factor Expression

Abstract: Pigment epithelium-derived factor (PEDF) is the most potent inhibitor of angiogenesis, suggesting that loss of PEDF contributes to proliferative diabetic retinopathy. However, the role of PEDF against retinal vascular hyperpermeability remains to be elucidated. We investigated here whether and how PEDF could inhibit the advanced glycation end product (AGE) signaling to vascular hyperpermeability. Intravenous administration of AGEs to normal rats not only increased retinal vascular permeability by stimulating v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 207 publications
(166 citation statements)
references
References 48 publications
8
158
0
Order By: Relevance
“…Parallel actions of high glucose and oxidative stress might inhibit the production of proteins that normally inhibit VEGF expression, enhancing this autocrine process. This hypothesis is supported by studies showing that decreased levels of endostatin and PEDF are correlated with increased VEGF levels in patients with diabetic retinopathy (Boehm et al, 2003;Funatsu et al, 2003) and that treatment with endostatin or PEDF can reduce VEGF-or AGE-induced retinal vascular permeability in vivo Yamagishi et al, 2006).…”
Section: Vegf Alternative Splicing-it Has Been Suggested That the Difmentioning
confidence: 73%
“…Parallel actions of high glucose and oxidative stress might inhibit the production of proteins that normally inhibit VEGF expression, enhancing this autocrine process. This hypothesis is supported by studies showing that decreased levels of endostatin and PEDF are correlated with increased VEGF levels in patients with diabetic retinopathy (Boehm et al, 2003;Funatsu et al, 2003) and that treatment with endostatin or PEDF can reduce VEGF-or AGE-induced retinal vascular permeability in vivo Yamagishi et al, 2006).…”
Section: Vegf Alternative Splicing-it Has Been Suggested That the Difmentioning
confidence: 73%
“…once daily in our model because we have previously found that (1) intravenous administration of 3.3 to 10 g PEDF/100 g b.wt. once a day exerts antithrombogenic, antipermeability, and anti-inflammatory effects in rats 16,23,24,29 ; (2) the peak concentration of circulating PEDF level is obtained at 2 hours after the 10 g PEDF injection/100 g b.wt. ; and (3) its level is increased to about 2-fold of basal level (from about 200 ng/ml to 400 ng/ml) in SD rats at 8 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Furthermore, VEGF not only has a crucial role in tumor angiogenesis and expansion but it could also evoke inflammatory reactions in tumors. [30][31][32][33][34][35] As we have previously shown that VEGF is induced by engagement of RAGE with AGE, 24,26 we studied the effects of AGE-aptamer on angiogenesis and macrophage infiltration in G361 melanoma and then investigated the involvement of AGE-RAGE-VEGF axis in anti-tumor actions of aptamer. For this, we first examined the effects of AGE-aptamer on expression levels of CD31 and Mac-3, markers of capillary endothelial cells and macrophages, respectively.…”
Section: Effects Of Age-aptamer On Tumor Growth In Nude Micementioning
confidence: 99%
“…24 In brief, BSA (25 mg/ml) was incubated under sterile conditions with 0.1 M glyceraldehyde in 0.2 M NaPO 4 buffer (pH 7.4) for 7 days. Then unincorporated sugars were removed by PD-10 column chromatography and dialysis against phosphate-buffered saline.…”
Section: Western Blotting Analysismentioning
confidence: 99%